PENGARUH PENGGUNAAN APLIKASI AKUNTANSI BERBASIS DIGITAL TERHADAP KUALITAS INFORMASI AKUNTANSI DAN KINERJA USAHA PADA UMKM - Aryanto, Aryanto; Farida, Ida; Ramahdani, Anisa (Pusat P2M Politeknik Negeri Batam, 2023)
The specific objective of this research is to analyze the effect of the use of digital accounting on the quality of accounting information produced, the effect of using digital-based accounting on business performance, the effect of the quality of accounting information on business performance, and the mediating effect of the quality of accounting information on the relationship between the use of digital accounting on the performance of MSMEs. This study uses quantitative data types sourced from primary data from questionnaires. Respondent population from UMKM in Tegal City with sampling technique using purposive sampling. Structural Equation Model (SEM) test data analysis method. The results showed that the use of digital accounting did not have a significant effect on the quality of accounting information, the use of digital accounting had a positive and significant effect on business performance, the quality of accounting information had no significant effect on business performance, and the quality of accounting information was not able to mediate the effect of using digital accounting on business performance. This study provides an overview of the effect of using digital accounting applications on MSMEs so that they can be a reference for encouraging digitization in MSMEs.